Research on Calculation and Simulating Analysis of Cycloidal Pin Wheel Meshing Stiffness - Su Jianxin; Wang Dongfeng; Xu Jiake; Zhang Jing; Li Hongji; Lü Ruifang (Jixie chuandong)
In order to further improve the load-bearing performance of the RV reducer, a force analysis is conducted on the cycloidal pin wheel pair, regarding the contact stress and meshing stiffness of the cycloidal pin wheel as the research objective functions. In order to optimize its load-bearing performance, a mathematical analysis model of contact stress and meshing stiffness is proposed regarding the important structural parameters of cycloidal and pin wheel, as the design variables such as needle tooth distribution circle radius, eccentricity, and needle tooth radius, VB.NET Software is applied to calculate and analyzes the influence of structural parameters of the cycloidal and pin wheel on the meshing stiffness, contact stress, meshing force, and torsional stiffness of the cycloidal and pin wheel pair. The results of calculation and simulation indicate that the meshing stiffness and torsional stiffness of cycloidal and pin wheel increase with the increase of the radius of the distribution circle and eccentricity the decrease of the radius of the teeth. The research provides theoretical foundation for the design and optimization of the structure of cycloidal and pin wheel reducers.